Planting date and plant density effects on flower abortion, fruit yield and seed quality of two varieties of chilli pepper (capsicum frutescens l.) in Ghana - Mends-Cole, Morleeta Teta (2016)
A thesis submitted to The School of Graduate Studies, Kwame Nkrumah University of Science And Technology in partial fulfillment of the requirements for the degree of Master of Philosophy In Seed Science and Technology, 2015